Corporate Financial Decisions, Financial Stability, and Firm Value in Indonesian Manufacturing Firms - Sugeng Haryanto; Retna Safriliana; Nanda Arsy Mutiah; Muhammad Umar Ariefudin; Yanuar Bachtiar (Petra International Journal of Business Studies, 2025)
This study aims to analyze the effect of corporate financial decisions on firm value, with financial stability as a moderating variable. Firm size and firm age variables are used as control variables. Financial decisions consist of investment decisions, financing decisions, and dividend decisions. We include firm size and firm age as control variables. This study was conducted on manufacturing companies that went public on the Indonesian Stock Exchange. This study was conducted on manufacturing companies that went public on the IDX. The number of company samples was 123, and the number of analysis data was 1,230. The analysis technique used was moderated regression analysis (MRA). The study's findings indicate that financial decisions have a positive effect on firm value. Financial stability is able to strengthen the company's financial decisions on firm value. The study's findings show that corporate stability is essential information for investors.